FINAL REPORT - NU CORPORATE WEB PORTAL - Omarov, Assylzhan; Kunbolsyn, Alisher; Nuraly, Marlen; Batmanov, Dinmukhamet; Ibrasheva, Nazira (Nazarbayev University School of Engineering and Digital Sciences, 2025)
The NU Corporate Web Portal project addresses the issue of having a centralized, university-level solution for handling institutional data, events, and services for students, teachers, and administrative staff members at Nazarbayev University. The initial objective was to develop an extensible and secure full-stack application that simplifies event planning, communication, and access to resources based on the user's role. The system includes news moderation, file storage, venue booking, and responsive design with Spring Boot and PostgreSQL as its base, and deployment on Docker via Render. The user interface is role-based, serving students, DSS staff, teachers, and general staff with similarly focused access and features.
Keywords: TECHNOLOGY::Information technology::Computer science; TECHNOLOGY::Information technology::Computer science::Software engineering; Corporate portal; Web development; type of access: open access